High-precision reconstruction of a heat flux boundary via a programmable scanning electron beam controlled by the voltage waveform design method - Minfeng Dou; Xiyao Wang; Hongxin Yao; Linshuang Long; Guozhu Zhao; Hong Ye (Case Studies in Thermal Engineering, 2024)
A scanning electron beam can be used to construct heat flux boundaries (HFBs). However, the long current response time in the deflection coil using a current control method (CCM) cause the deviation of the current waveform, potentially reducing the accuracy of the reconstructed HFB relative to the target HFB. The impact of the current response time on the reconstruction accuracy increases as the field frequency increases, and the accuracy can be reduced from 0.89 to 0.69. To shorten the current response time and improve the reconstruction accuracy, a voltage waveform design method (VWDM) is introduced as a replacement for the CCM. The result indicates that the accuracy of the HFB reconstructed by a scanning electron beam controlled by the VWDM can reach 0.91. Additionally, increasing the maximum output voltage of the power amplifier used to generate the voltage can further improve the reconstruction accuracy of the HFB with the VWDM. This study provides a new approach for the accurate construction of HFBs for rapid thermal processing, additive manufacturing and thermal assessment of hypersonic vehicles.